Leak Detection in Medium Density Polyethylene Pipeline using Ensemble Empirical Mode Decomposition Method - Gigih Priyandoko (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2021)
A water resource is an important element in the contemporary society life.  In global world water loss or water leaking can vary between 10% to 40% of total water volume produced.  A traditional method such as visual inspection can be operates but that method required a long time. The objectives of the research to identify the occurrence of leaks and know its exact location in the pipeline by using specific method which are acoustic leak detection method and transient method. An EEMD method will be applied as the analysis method to collect and analyses the data. Based on the experimental results that the EEMD analysis predict satisfactorily the location in MDPE pipeline as it can detect and locate the leak up to error of 4.09% and 0.61%. The EEMD method had the best perform and already produce an acceptable result.